Impact of Completing CLEFT-Q Scales That Ask About Appearance on Children and Young Adults: An International Study. (July 2020) - Klassen, Anne F.; Dalton, Louise; Goodacre, Timothy E. E.; Harman, Karen E.; Slator, Rona; Tsangaris, Elena; Courtemanche, Douglas J.; Goldstein, Jesse; Allen, Gregory C.; Mahony, Aisling O.; Riff, Karen W. Y. Wong
Objective: To describe the impact of completing the CLEFT-Q appearance scales on patients with cleft lip and/or palate and to identify demographic and clinical characteristics and CLEFT-Q scores associated with reporting a negative impact. Design: International cross-sectional survey. Setting: Recruitment took place between October 2014 and November 2016 at 30 craniofacial clinics located in 12 countries. Patients: Aged 8 to 29 years with cleft lip and/or palate. Main Outcome Measure(s): Participants were asked 4 questions to evaluate the impact of completing the field test version of a patient-reported outcome measure (the CLEFT-Q) that included 154 items, of which 79 (51%) asked about appearance (of the face, nose, nostrils, teeth, lips, jaws, and cleft lip scar). Results: The sample included 2056 participants. Most participants liked answering the CLEFT-Q (88%) and the appearance questions (82%). After completing the appearance scales, most participants (77%) did not feel upset or unhappy about how they look, and they felt the same (67%) or better (23%) about their appearance after completing the questionnaire. Demographic and clinical variables associated with feeling unhappy/upset or worse about how they look included country of residence, female gender, more severe cleft, anticipating future cleft-specific surgeries, and reporting lower (ie, worse) scores on CLEFT-Q appearance and health-related quality-of-life scales. Conclusion: Most participants liked completing the CLEFT-Q, but a small minority reported a negative impact. When used in clinical practice, CLEFT-Q scale scores should be examined as soon as possible after completion in order that the clinical team might identify patients who might require additional support.